2009
DOI: 10.1016/j.apergo.2008.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pen design on drawing and writing performance

Abstract: Two experiments are reported with the aim of determining the effect of pen shape and size on two different types of task: drawing and writing. Experiment 1 attempted to determine the optimum shape and size of shank for ball-point pens used to perform an accurate drawing task. Twenty-seven participants used a total of nine different pens. Drawing performance was measured by having the subjects follow mazes of different size. The dependent variables were drawing movement time and drawing accuracy. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Further, movements in curved and irregular paths (Montazer et al 1988;Goonetilleke et al 2009) have also been investigated where movement direction changes. The changes in movement time have been attributed to the changes in muscle groups used, as movement angle is varied.…”
Section: Introductionmentioning
confidence: 99%
“…Further, movements in curved and irregular paths (Montazer et al 1988;Goonetilleke et al 2009) have also been investigated where movement direction changes. The changes in movement time have been attributed to the changes in muscle groups used, as movement angle is varied.…”
Section: Introductionmentioning
confidence: 99%
“…Goonetilleke et al [122] state that writing speed is not affected by pen shape, but accuracy is highest when using slim, circular pens. With the rise of Smartphones and mobile devices, signing with fingers is expected to become more common.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The pen mouse is elliptical in cross section shape and has dimensions of 21 mm × 16.3 mm. Researchers [40] have shown that accuracy of a tracking task is best when a circular probe is used having a diameter of about 8 mm. In contrast, the stylus of the tablet has a circular cross section and a diameter of 12.2 mm, closer to the optimum values for minimum tracking error.…”
Section: Errorsmentioning
confidence: 99%